TRIM3 attenuates cytokine storm caused by Dabie bandavirus via promoting Toll-like receptor 3 degradation - Jin, Ke; Dai, Yan; Ouyang, Ke; Huang, Huaying; Jiang, Zhengyi; Yang, Zhan; Zhou, Tingting; Lin, Hong; Wang, Chunhui; Wang, Chunyan; Sun, Xuewei; Lu, Dafeng; et al. (Frontiers in Microbiology, 2023)
Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that was caused by the Dabie bandavirus (DBV), and it has become a global public health threat. Cytokine storm is considered to be an important pathogenesis of critical SFTS. Tripartite motif-containing 3 (TRIM3), as a member of the TRIM protein family, may contribute to the regulation of the immune and inflammatory responses after viral infection. However, whether TRIM3 plays a major role in the pathogenesis of SFTS has not yet been investigated. Methods TRIM3 mRNA levels were detected in PBMCs between 29 SFTS patients and 29 healthy controls by qRT-PCR. We established the pathogenic IFNAR−/− SFTS mouse model successfully by inoculating subcutaneously with DBV and testing the expression levels of TRIM3 mRNA and protein by qRT-PCR and immunofluorescence in the livers, spleens, lungs, and kidneys. TRIM3OE THP-1 cells and peritoneal macrophages extracted from TRIM3−/− mice were infected with DBV. The effect of TRIM3 on cytokines was detected by qRT-PCR and ELISA. Then we examined Toll-like receptor 3 (TLR3) and protein phosphorylation in the MAPK pathway after DBV infection using Western blot. Flow cytometry was used to verify TLR3 expression on peripheral blood monocytes in SFTS patients. We further explored the interaction between TRIM3 and TLR3 using CO-IP and Western blot. Results Compared to healthy controls, TRIM3 mRNA expression in PBMCs is decreased in SFTS patients, especially in severe cases. TRIM3 mRNA and protein were synchronously reduced in the livers, spleens, lungs, and kidney tissues of the IFNAR−/− SFTS mice model. In the DBV-infected cell model, TRIM3 overexpression can inhibit the DBV-induced release of IL-1β, IL-6, and TNF-α, the expression of TLR3, and protein phosphorylation in the MAPK pathway, which plays an anti-inflammatory role, while TRIM3 deficiency exacerbates the pro-inflammatory effects. We further found that TRIM3 can promote TLR3 degradation through K48-linked ubiquitination. Conclusion TRIM3 can inhibit the production of cytokines by regulating the degradation of TLR3 through K48-linked ubiquitination, which can be a therapeutic target for improving the prognosis of SFTS.